Interlaboratory comparison measurements of aspheres. (9th April 2018) - Schachtschneider, R; Fortmeier, I; Stavridis, M; Asfour, J; Berger, G; Bergmann, R B; Beutler, A; Blümel, T; Klawitter, H; Kubo, K; Liebl, J; Löffler, F; et al.
Abstract: The need for high-quality aspheres is rapidly growing, necessitating increased accuracy in their measurement. A reliable uncertainty assessment of asphere form measurement techniques is difficult due to their complexity. In order to explore the accuracy of current asphere form measurement techniques, an interlaboratory comparison was carried out in which four aspheres were measured by eight laboratories using tactile measurements, optical point measurements, and optical areal measurements. Altogether, 12 different devices were employed. The measurement results were analysed after subtracting the design topography and subsequently a best-fit sphere from the measurements. The surface reduced in this way was compared to a reference topography that was obtained by taking the pointwise median across the ensemble of reduced topographies on a 1000 × 1000 Cartesian grid. The deviations of the reduced topographies from the reference topography were analysed in terms of several characteristics including peak-to-valley and root-mean-square deviations. Root-mean-square deviations of the reduced topographies from the reference topographies were found to be on the order of some tens of nanometres up to 89 nm, with most of the deviations being smaller than 20 nm. Our results give an indication of the accuracy that can currently be expected in form measurements of aspheres.